Letter - Penge & Beckenham Joint Strike Committee Trades and Labour Club, n.d. (Penge)
"Letter - Penge & Beckenham Joint Strike Committee Trades and Labour Club, n.d." [g0219001.jpg], n.d. Local Organisation